Tracking the elusive history of diversification in plant–herbivorous insect–parasitoid food webs: insights from figs and fig wasps. Issue 4 (February 2016) - Kjellberg, Finn; Proffit, Magali
Abstract : The food webs consisting of plants, herbivorous insects and their insect parasitoids are a major component of terrestrial biodiversity. They play a central role in the functioning of all terrestrial ecosystems, and the number of species involved is mind‐blowing (Nyman et al .2015 ). Nevertheless, our understanding of the evolutionary and ecological determinants of their diversity is still in its infancy. In this issue of Molecular Ecology, Sutton et al . (2016 ) open a window into the comparative analysis of spatial genetic structuring in a set of comparable multitrophic models, involving highly species‐specific interactions: figs and fig wasps. This is the first study to compare genetic structure using population genetics tools in a fig‐pollinating wasp ( Pleistodontes imperialis sp1) and its main parasitoid ( Sycoscapter sp.A). The fig‐pollinating wasp has a discontinuous spatial distribution that correlates with genetic differentiation, while the parasitoid bridges the discontinuity by parasitizing other pollinator species on the same host fig tree and presents basically no spatial genetic structure. The full implications of these results for our general understanding of plant–herbivorous insect–insect parasitoids diversification become apparent when envisioned within the framework of recent advances in fig and fig wasp biology.